Dampak Melemahnya IHSG terhadap Stabilitas Ekonomi Nasional - Muh. Syata, Wahyu (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research discusses the impact of the weakening of the Composite Stock Price Index (IHSG) on Indonesia’s national economic stability. The Composite Stock Price Index (IHSG) serves as a key indicator of investor confidence and stock market performance, where a significant decline can reflect disruptions in economic stability. Various internal and external factors, such as inflation, interest rates, and geopolitical tensions, contribute to the fluctuations of the IHSG. This research uses a descriptive qualitative approach through literature study, by reviewing various relevant bibliographic sources. The decline in the IDX Composite Index can trigger a wealth effect that reduces public consumption, as well as hinder investment and company expansion. This has the potential to worsen economic conditions, increase unemployment, and reduce the purchasing power of the public. To address these negative impacts, coordination between fiscal and monetary policies is necessary. Expansive fiscal policies and interest rate cuts by Bank Indonesia can drive economic growth and rebuild market confidence. This research is expected to provide a comprehensive understanding of the relationship between the IDX Composite Index (IHSG) and economic stability, as well as the policy implications that need to be considered to maintain national economic sustainability.